(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2022)
The purpose of this article is to show how abortion stems from a mimetic desire and which, even today, generates a crisis and violence on the part of a population against the helpless fetus, which becomes the scapegoat, that is, the innocent victim. Of a mass society, built and educated to condemn those who, in addition to having no voice, have their rights subjugated. The violence perpetrated and instigated against these innocent people is practiced not only by those who generate them, but by the collective that acts irrationally, feeding the destructive cycle of violence daily. These helpless beings are a symbol of human sacrifice that is perpetuated in a camouflaged and often disguised way in our midst and, as an abortion provisionally resolves the mimetic crisis, others need to multiply as a way of cherishing that group that believes to be this is the solution to peace.